The Effect of Oral and Intraperitoneal Administration of Acorus calamus L. Extract on Learning and Memory in Male Rats - GA Naderi; M Khalili; M Karimi; M Soltani (Institue of Medicinal Plants, ACECR, 2010)
Background: Learning and memory impairment during aging mind have a disturbance role in human life. Regarding to the defect mechanisms for prevention or treatment of memory loss, the new strategies were recommended for study on it. Objective: Importance of herbal medicine treatment encouraged us to examine the effect of a candidate plant Acorus calamus for improvement of learning and memory. Methods: Male rats were randomly divided to control and treatment groups. In treatment group the plant were applied to animals in oral (plant/ food ratio = % 6.25) for two weeks and in injected groups the plant extract were applied (i.p) to rat in 25, 50 and 100 mg/kg). Finally, all experimental animal groups were conducted to Y maze and shuttle box tests in order to obtain spatial recognition and acquisition - recalling data, respectively. Results: The step through latency (STL) time resulted from oral and 100 mg/kg injected dose groups show a significant difference with control animals. Also, alternation behavior (%) obtained from Y maze test data was marked than control rats. Conclusion: The present study show that oral and intraperitoneal administration of the extract in higher dose could have increase spatial recognition and recalling the data,